Compendium of Transgenic Crop Plants 2008
DOI: 10.1002/9781405181099.k0307
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Beans

Abstract: Vigna species of the subgenus Ceratotropis constitute an economically important group of cultivated and wild species, of which a rich diversity occurs in Asian subcontinent. Progress in genetic improvement in Vigna species has been made mainly by conventional breeding methods. These methods, in addition of being time‐consuming and labor‐intensive, are met with a wide range of problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…At 10 sec sonication time, a large number of microwounds were produced across the tissue, which permitted the Agrobacterium to penetrate deeper and more completely throughout the tissue as compared to the natural infection obtained during co-cultivation, thus improving the bacterial colonization and infection of the tissue [ 36 ]. Trick and Finer [ 37 ] observed under SEM that ultrasound treatment produced small wounds, which allowed Agrobacterium access to internal plant tissue. Sahoo and Jaiwal [ 38 ] reported that the sonication treatment has the potential to increase transformation efficiency by improving penetration of Agrobacterium cells into the cell layers beneath the epidermis of the cotyledonary node region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 10 sec sonication time, a large number of microwounds were produced across the tissue, which permitted the Agrobacterium to penetrate deeper and more completely throughout the tissue as compared to the natural infection obtained during co-cultivation, thus improving the bacterial colonization and infection of the tissue [ 36 ]. Trick and Finer [ 37 ] observed under SEM that ultrasound treatment produced small wounds, which allowed Agrobacterium access to internal plant tissue. Sahoo and Jaiwal [ 38 ] reported that the sonication treatment has the potential to increase transformation efficiency by improving penetration of Agrobacterium cells into the cell layers beneath the epidermis of the cotyledonary node region.…”
Section: Resultsmentioning
confidence: 99%
“…Sahoo and Jaiwal [ 38 ] reported that the sonication treatment has the potential to increase transformation efficiency by improving penetration of Agrobacterium cells into the cell layers beneath the epidermis of the cotyledonary node region. SAAT has been playing a vital role in improving the transformation frequency and provided efficient delivery of T-DNA into cells in many plant species [ 39 , 40 ], especially those that are typically more recalcitrant to Agrobacterium -mediated transformation [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although grass pea is endowed with many good features, the production of the species has not yet improved significantly due to its prominent susceptibility to biotic and abiotic stresses (Jaiwal & Gulati, 1995;Sahoo & Jaiwal, 2008). Physiological and molecular mechanism of its adaptation to different abiotic stresses are still not well studied (Piwowarczyk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high protein content and perfect combination of all nutrients, including proteins (25-26 %), carbohydrates (60 %), fat (1.5 %), minerals, amino acids and vitamins (Karamany 2006), it is extensively used in Asia especially in India and now also grown in the Southern United States, the West Indies, Japan and other tropics and subtropics (Delic et al 2009). Viral and fungal pathogens lead to severe yield losses in blackgram (Sahoo and Jaiwal 2008) and to overcome this problem, attempts have been made to obtain resistant cultivars either by conventional breeding or genetic transformation. Due to limited genetic variation among cultivated accessions and sexual incompatibility with wild relatives, genetic engineering is a good alternative for conventional breeding.…”
Section: Introductionmentioning
confidence: 99%